(untitled) (TAMADDUN NURI JURNALI, 2024)
This article explores the complex phenomenon of word borrowing in linguistics, emphasizing its multifaceted theoretical foundations and processes. It is highlighted the adaptation of borrowed words to the phonetic, semantic, grammatical, and orthographic systems of the receiving language.